Experimental verification of a new method of calculation for pressure distributive pipelines - Chernyuk, Volodymyr V.; Orel, Vadym I. (Oficyna Wydawnicza Politechniki Rzeszowskiej, 2009)
In comparison with all the known methods of calculation for pressure distributive pipelines (PDP), those developed by Chernyuk,V.V. proved to most exactly agree with results of experiments. Calculated by this technique values of flow rate and of heads of fluid inside PDP practically coincide with experimental data.
Keywords: pressure distributive pipelines; variable mass fluid flow